Acute peripheral facial paralysis following varicella infection: An uncommon complication - Damla Hanalioğlu; Yasemin Özsürekci; Ayşe Büyükçam; Ayşe Gültekingil-Keser; Özlem Tekşam; Mehmet Ceyhan (The Turkish Journal of Pediatrics)
Chickenpox is caused by varicella zoster virus (VZV/HHV-3), which is one of the eight human herpes viruses. Although chickenpox has a good prognosis, neurologic complications including encephalitis, acute cerebellar ataxia, myelitis and meningitis may seldom be associated with the disease. Peripheral facial palsy (PFP) is an extremely rare complication in patients with chickenpox. Herein, we report a 12-year-old boy with chickenpox and unilateral peripheral facial palsy, who was successfully treated with short-term steroids and physical rehabilitation.